Perbandingan Konsep Negara Islam : Analisis Pemikiran Syekh Taqiyuddin An-Nabhani dan KH. Abdurahman Wahid - Muhammad Hasanal Muid; Heri Kusmanto; Indra Fauzan (PERSPEKTIF, 2023)
This paper examines two concepts of ideal state thought according to Sheikh Taqiyuddin an-Nabhani and KH. Abdulrahman Wahid. According to KH. Abdurahman Wahid, the Islamic state is the Pancasila state that exists today in the Unitary State of the Republic of Indonesia because in addition to Pancasila containing the concept of monotheism in its first precepts, it is also because Islam is a religion that highly values diversity and plurality. Meanwhile, according to Sheikh Taqiyuddin an-Nabhani what is called an Islamic state is a state with the form of a Khilafah because according to him only with a Khilafah all Islamic teaching can be implemented perfectly. This paper compares, reviews and critiques each of these thoughts so that it is hoped that there will be a new finding from these two contrasting thoughts. The results of the research show that the debate about an Islamic state has not yet reached a single point of agreement. In fact, discussions about the concept of an Islamic state are always interesting to study to serve as a reference source for existing treasures of political thought.